Code-Switching in Early English. - Schendl, Herbert (Topics in English linguistics ;, 2011)
The frequent mixing of different languages in early English texts, especially Latin, English and French, has been neglected by historical English linguistics. The contributions in this volume approach this phenomenon within the framework of code-switching theory and, based on a variety of text types from Old to early modern English, show the relevance of these texts for the history of English as well as for historical and general linguistics.